Revitalisasi Pemikiran Pendidikan Islam Ibnu Khaldun dalam Konteks Pendidikan di Era Modern (Analisis Studi Kasus di Pesantren Syaikh Zainuddin NW Anjani) - M. Tabibuddin; Muhamad Alwi Muhtar; Syamsul Arifin (Journal on Education, 2024)
This research examines the revitalization of Ibn Khaldun's Islamic educational philosophy within the context of Pesantren Syaikh Zainuddin NW Anjani in the modern era. Ibn Khaldun, a 14th-century Muslim scholar, held a comprehensive view of education that encompassed social, cultural, and psychological aspects. This case study aims to explain how Ibn Khaldun's concepts, such as 'Asabiyyah,' 'Tarbiyah,' and 'Umran,' can be applied in modern education within pesantren. The research methodology includes interviews, observations, and document analysis. The results show that Pesantren Syaikh Zainuddin NW Anjani has successfully integrated Ibn Khaldun's philosophy into its curriculum and educational practices. 'Asabiyyah' is used to foster social solidarity, while 'Tarbiyah' shapes the character of students. This research holds significant implications for the development of Islamic education in the modern era and promotes the continuity of Islamic values in education